2014
DOI: 10.1007/s11102-014-0608-3
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of somatostatin analogs while acromegaly is in long-term remission

Abstract: The final GH levels prior to discontinuation of SRL should be taken into consideration in patients with acromegaly in long-term remission. Moreover, the first visit 3 months after withdrawal is critically important for determining the future status of remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
2
17
2
Order By: Relevance
“…This is in marked contrast with our study, where only 2 of 58 patients (3.4%) had been on similarly long dose intervals, and also in contrast with the other three studies, where such dose intervals were used in 10-11% of patients [12,14] or were not used at all [13] . In addition, the inclusion of patients using cabergoline in combination with SAs in one of those studies seems inappropriate to characterize remission after SA withdrawal [13] .…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…This is in marked contrast with our study, where only 2 of 58 patients (3.4%) had been on similarly long dose intervals, and also in contrast with the other three studies, where such dose intervals were used in 10-11% of patients [12,14] or were not used at all [13] . In addition, the inclusion of patients using cabergoline in combination with SAs in one of those studies seems inappropriate to characterize remission after SA withdrawal [13] .…”
Section: Discussioncontrasting
confidence: 97%
“…These figures are lower than the 18.5-20% remission rates found in three other studies [12][13][14] and much lower than the 42% reported in one single report [15] , but these percentage rates are derived from proportions (5/27, 4/20, 3/16, and 5/12, respectively) obtained from smaller sample sizes than in our study. In addition, these figures should not be compared without carefully analyzing differences in inclusion and remission criteria between studies.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Most studies have found that the disease is likely to recur soon after discontinuation, although some studies have found that GH and IGF1 levels remain at safe levels in a small subset of patients even after treatment discontinuation (4, 9, 10, 11). Based on the limited data currently available (mostly case reports/series), it appears that remission after discontinuation of medical treatment may be more likely in patients with low GH and IGF1 levels before treatment withdrawal, in those who respond well to low-dose treatment, in patients without adenoma on magnetic resonance imaging (MRI) and/or in patients receiving prolonged treatment (3, 12, 13, 14). Nonetheless, the characteristics of patients likely to achieve sustained remission after treatment discontinuation are still not well understood.…”
Section: Introductionmentioning
confidence: 99%